2018
DOI: 10.1371/journal.pone.0192689
|View full text |Cite
|
Sign up to set email alerts
|

Gene set analysis of post-lactational mammary gland involution gene signatures in inflammatory and triple-negative breast cancer

Abstract: BackgroundEpidemiological studies have found that triple-negative breast cancer (TNBC) and TN inflammatory breast cancer (IBC) are associated with lower frequency and duration of breast-feeding compared to non-TNBC and non-TN IBC, respectively. Limited breast-feeding could reflect abrupt or premature involution and contribute to a “primed” stroma that is permissive to the migration of cancer cells typical of IBC. We hypothesized that gene expression related to abrupt mammary gland involution after forced weani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 36 publications
4
22
0
Order By: Relevance
“…In that study the control group were cancer-free women, in our study the control group were non-IBC patients, and there was no role of long duration of breastfeeding in the TN group. Previous studies have found that TN breast cancer and TN IBC are associated with lower frequency and duration of breastfeeding compared to non-TN breast cancer and non-TN IBC, respectively [10]. Reproductive risk factors and TN breast cancer have also been observed in other studies [11,12].…”
Section: Discussionmentioning
confidence: 72%
“…In that study the control group were cancer-free women, in our study the control group were non-IBC patients, and there was no role of long duration of breastfeeding in the TN group. Previous studies have found that TN breast cancer and TN IBC are associated with lower frequency and duration of breastfeeding compared to non-TN breast cancer and non-TN IBC, respectively [10]. Reproductive risk factors and TN breast cancer have also been observed in other studies [11,12].…”
Section: Discussionmentioning
confidence: 72%
“…Pregnancy associated histological changes in the mammary tissue are induced by steroid hormones and growth factors 12 . When this influence diminishes, epithelial cells undergo a massive programmed cell death and tissue remodeling, so called post‐lactational involution 47 . It is hypothesized that post‐lactational involution increases the number of microcalcification clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our data presented herein showing that SEMA7A is increased during involution, we are investigating whether SEMA7A is a primary driver of postpartum breast cancer aggressiveness in our University of Colorado Young Women’s cohort (46). Interestingly, a recent in silico analysis revealed two involution gene signatures that were significantly upregulated in inflammatory breast cancer (IBC)(47). IBC is a highly aggressive type of breast cancer that is characterized by tumor emboli in dermal lymphatics, which is reminiscent of what we have observed in mammary lymphatics of our postpartum patients(10)(Figure 6E).…”
Section: Discussionmentioning
confidence: 99%